Mathematics Academic Performance: Multiple Regression Analysis Model - Barrera, Janet D. (Future Science / FSH-PH Publications, 2024)
A multiple regression model was established based on the examination of factors of academic performance among BSEd Mathematics students during the academic year 2023-2024 of J.H. Cerilles State College-Dumingag Campus. The data of the participants’ perceptions of the extent of teachers’ support, instructional competence, and participants’ academic engagement were examined to determine if these constituted factors of students’ academic performances. This study employed a quantitative design, utilizing multiple regression analysis. Adapted questionnaire checklists were used, and data were analyzed using a five-point Likert scale. A reliability test using the Cronbach alpha coefficient was determined using Jamovi software. The study included students from the first to fourth year of BSEd Mathematics at J.H. Cerilles State College-Dumingag Campus, Dumingag, Zamboanga del Sur, who are currently pursuing a Bachelor of Secondary Education major in Mathematics for the academic year 2023-2024. The weighted arithmetic mean, frequency, and percentage distribution were used to treat the descriptive questions. The study revealed that the teachers provided a high level of support to students’ mathematics learning and were competent in providing quality instructions among mathematics students. The students exhibited a high level of academic engagement; and performed well in their mathematics major subjects. Teachers’ support, instructional competence, and student academic engagement were significant correlates of mathematics students’ academic performances. The high level of teacher’s support is manifested in the way the teachers encourage the students to explore more problem-solving exercises and assist them whenever they encounter difficulties. The teacher’s instructional competence is evident when they encourage students’ interest, motivation, and participation. There is a high level of academic engagement when the students practice more drills. The students acquired skills and competences in math learning areas. The study recommends that the students may promote self- directed learning and motivation among students to improve their academic engagement and performance in mathematics; the mathematics educators may implement strategies to increase academic engagement through fostering individual tasks and collaboration to develop students’ mathematics skills and dependence; the curriculum designers may design mathematics curricula align with educational standards that promote the development of essential mathematics competencies among students; the school administrators may foster a collaborative school that emphasizes the importance of mathematics education and supports ongoing research and innovation in teaching practices; the parents may advocate for parental involvement in actively supporting children’s mathematical learning by providing resources, creating a supportive home environment, and reinforcing the value of mathematics education; and the future researchers may Investigate effective strategies and interventions for enhancing mathematics education and improving student outcomes in the subject. Mathematics is a crucial subject in education, providing students with essential knowledge and skills. To boost academic performance, teachers need to provide intensive support, instructional competence, and student engagement. Siddiqi (2018) found a significant relationship between teachers' effort and students' academic progress, advocating for improved instruction-based classroom learning and good teacher-student connections.